Inhibition of gastric acid secretion in the dog by the H2-receptor antagonists, ranitidine, cimetidine, and metiamide. Issue 5 (May 1980) - Daly, M J; Humphray, J M; Stables, R
Abstract : The new H2-receptor antagonist, ranitidine, has been compared with cimetidine and metiamide as an inhibitor of gastric acid secretion in the dog. All three compounds were effective both intravenously or by mouth in inhibiting secretion induced by histamine, pentagastrin, or bethanechol. This inhibition was mainly attributable to a reduction in the volume of secretion, although there was also a significant reduction in the concentration of acid secreted. Metiamide was slightly less active than cimetidine, but ranitidine was four to nine times more potent than cimetidine, depending on the secretagogue used. The antisecretory activity of ranitidine does not result from a limitation in blood flow to the gastric mucosa.